Reformulasi Pengaturan Prapenuntutan dalam Rancangan Kitab Undang-Undang Hukum Acara Pidana (RKUHAP) untuk Menjamin Keadilan dan Kepastian Hukum pada Proses Peradilan Pidana - Raihan Aridewa; Wahyu Priyanka Nata Permana (Fakultas Hukum Universitas Islam Indonesia, 2025)
The criminal justice system in Indonesia aims to uphold fair law and provide legal certainty. The pre-prosecution stage, which serves as a bridge between investigation and prosecution, plays a crucial role. However, its regulation in the Indonesian Criminal Procedure Code (KUHAP) is considered weak, with issues such as lack of investigator oversight, unclear evidence standards, and lengthy processes, potentially leading to legal uncertainty and human rights violations. The Draft Criminal Procedure Code (RKUHAP) proposes pre-prosecution reforms by strengthening the prosecutor's role as dominus litis, implementing strict time limits, and enhancing accountability. This study analyzes the problems in the implementation of pre-prosecution under the KUHAP and how the RKUHAP can ensure justice and legal certainty. The research uses a normative legal method with a legislative approach, utilizing legal sources such as laws, the RKUHAP draft, government regulations, as well as journals, literature, and relevant research findings related to the topic. The results indicate that the RKUHAP serves as a solution by proposing structural reforms, such as eliminating the term